2014
DOI: 10.1371/journal.pone.0102055
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction and Risk of End Stage Renal Disease Requiring Dialysis: A Nationwide Population-Based Study

Abstract: BackgroundPrevious studies have suggested that erectile dysfunction (ED) is an independent risk factor for macrovascular disease. Very few studies have evaluated the relationship between ED and risk of end stage renal disease (ESRD) requiring dialysis.MethodsA random sample of 1,000,000 individuals from Taiwan's National Health Insurance database was collected. We selected the control group by matching the subjects and controls by age, diabetes, hypertension, coronary heart disease, hyperlipidemia, area of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The incidence rate of ED was higher in TBI patients when compared with the non-TBI control group (24.66 and 19.07 per 100,000, respectively), or 0.09% (64 in 72,624) in the TBI subjects and 0.07% (146 in 217,872) in the non-TBI control. The incidence rate is similar to other studies using NHIRD for ED ( Kao et al, 2016 ; Shen, Weng, Wang, & Tien, 2014 ). The differences of prevalence rates among these studies might be related to the studies design.…”
Section: Discussionsupporting
confidence: 89%
“…The incidence rate of ED was higher in TBI patients when compared with the non-TBI control group (24.66 and 19.07 per 100,000, respectively), or 0.09% (64 in 72,624) in the TBI subjects and 0.07% (146 in 217,872) in the non-TBI control. The incidence rate is similar to other studies using NHIRD for ED ( Kao et al, 2016 ; Shen, Weng, Wang, & Tien, 2014 ). The differences of prevalence rates among these studies might be related to the studies design.…”
Section: Discussionsupporting
confidence: 89%
“…CKD can interfere directly with erectile function by decreasing penile arterial blood flow, affecting penile venous leakage due to shunts, altering penile smooth muscle function, and causing hormonal disturbances and/or neurogenic dysfunction ( 30 ). Indirectly, CKD impairs erectile function by requiring use of medications with many side effects (including ED) or linked to diabetes mellitus and/or systemic arterial hypertension, conditions that lead to endothelium dysfunction causing CKD and ED ( 1 , 3 , 8 , 9 , 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“… 17 Therefore, traditional risk factors that impair the vascular system include several systemic diseases such as diabetes mellitus, hypertension, dyslipidemia, end-stage kidney disease, cirrhosis of the liver, and coronary artery disease. 18 20 Several studies have also indicated that ED could be an early sign of endothelial dysfunction and microvascular disease. 21 23 …”
Section: Discussionmentioning
confidence: 99%